Konstruksi identitas politik gen z dalam ruang publik modern: studi kualitatif mengenai makna diskusi demokrasi di kafe modern - Dinejad, Muhammad Daffa (Maliki Interdisciplinary Journal, 2026)
Modern cafes in Malang have transformed into hybrid public spaces where Generation Z (Gen Z) can exchange ideas on democratic issues. This study, using a phenomenological approach, reveals five main findings: (1) Cafés function as a modified “third place,” neutralizing class hierarchies while maintaining privacy hierarchies; (2) They combine physical and digital interactions but face a digital validation paradox that can undermine individual self-confidence; (3) A shift from a popular public sphere toward an issue-partisan public sphere; (4) The café’s aesthetic creates legitimacy for political discourse; (5) Cafés become the infrastructure of Gen Z’s political identity. The study concludes that modern cafés facilitate hybrid, reflective, and autonomous political participation, and reconceptualize several theories of the public sphere within the context of digital-native Gen Z in Indonesia.